ANALISIS PENGARUH KEPUASAN DAN PERSEPSI HARGA TERHADAP CITRA RESTORAN DAN MINAT BELI ULANG PELANGGAN HOLYCOW SEMARANG - Adiputra, Febrian; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2016)
Every company wants consumers can re-purchase the company. Therefore, employers race - the race to attract consumers of various segments in accordance with the target market. This is done to make consumers who have come in and buy food at the restaurant, are interested in coming back to the restaurant one is Holycow in Semarang. Problems that occur in Holycow is there a decrease in the number of sales and an increase in the number of complaints during the end Â year 2014 and in the year 2015, which indicates an increase in customer dissatisfaction which cause customers not interested in re-purchase. Prasurvey based on the results that have been done, it can take several variables thought to influence the the image of the restaurant is customer satisfaction, and the perception of price. The purpose of this study was to analyze the factors that affect the image of the restaurant and customer repurchase intention Holycow Semarang.The study population was all subscribers restaurant Holycow Semarang. The sampling method used in this research is purposive sampling method. The sample used in this study were 96 people Holycow Semarang restaurant customers. The data used are primary data using questionnaires. The analysis technique used is the analysis path analysis with Sobel test.Based on this research results by using determination , the image of the restaurant is able to be explained by two variables: customer satisfaction and perception of prices by 76.6 % . Buying interest re able to be explained by the perception and image of the restaurant price of 71.7 %